Potential coconut (Cocos nucifera) hybrids developed using Gangabondam (GBGD) as maternal parent for yield and quality for southern dry tract of Karnataka (India) - SUMITHA, S; MAHESWARAPPA, H P; BASAVARAJU, T B; PRASHANTH, M; SWETHA, SWETHA (The Indian Journal of Agricultural Sciences, 2020)
A long term evaluation of nine coconut (Coconut nucifera L.) hybrids with a local check was conducted under irrigated conditions at All India Coordinated Research Project on Palms, Horticulture Research Station, Arsikere, Karnataka. The experimental material consisted of nine hybrids with different cross combinations, viz. Tall × Tall, Tall × Dwarf and Dwarf × Tall along with TPT (Tiptur Tall) as local check planted during 1987-1988 and evaluated for yield performance for a period of 18 years (till 2015-16). Among the nine coconut hybrids evaluated, the cross combinations involving dwarf as female parent (Gangabondam) and tall cultivars as male parent, viz. GBGD × LCOT, GBGD × PHOT and GBGD × FJT performed superior and recorded significantly higher nut yield (128.6, 124.3 and 110.3 nuts palm-1 year-1, copra yield 22.0, 19.8 and 16.3 copra kg palm-1 year-1), with oil yield ranged from 11.5 to 13.8 kg palm-1 year-1when compared to local check. Hybrids possessed higher quantity of organoleptically ’good’ tender nut water (326 to 395.4 ml) with TSS of 5.6 to 6.2 °Brix , 26.0 to 31.6 ppm of sodium and 2025.1 to 2110.1 ppm of potassium.